'Creating insurrections in the heart of our country:' fear of the British West India Regiments in the Southern US Press, 1839–1860. (3rd July 2018) - Narayan, Rosalyn
ABSTRACT: In the decades leading to the Civil War, the United States and Great Britain faced a number of diplomatic crises, during which southern politicians often became alarmed at the prospect of British soldiers invading the southern coastline. The perceived threat was part of a wider southern paranoia over Britain's role in what was seen as a conspiracy to demolish the southern American system of slavery for Britain's ultimate economic gain. The alarm over an imagined British invasion was exacerbated by the fact that the anticipated invaders were free black men, the West India Regiments, stationed in the British West Indies. The tone of this paranoia was shaped by the memory of black participation in the War of 1812 and the fear that slaves would flee to British lines in any future conflict. An analysis of the discourse about these men in the southern press tells us much about the fears of southern slaveholders with regard to the trustworthiness of their own slaves and the ever-present threat of slave rebellion. Ultimately, the fears expressed about a disciplined black army led by an abolitionist imperial power reveal the true nature of southern anxiety over the stability of the South's own form of white supremacy.